Exploring the multiple dimensions of social support among elite female adolescent swimmers - Hassell, K.; Sabiston, C. M.; Bloom, G. A. (International Journal of Sport Psychology, 2010)
This study concurrently explored multiple dimensions of social support of nine elite female adolescent swimmers. Data were collected and analyzed using the principles of constructivist phenomenology. Results highlighted the importance of the structural, functional, and perceptual social support dimensions on athletes` experiences in elite swimming in relation to their coaches, parents, and peers. Coaches were an important provider of almost every aspect of social support. Parents provided social support on a more general level, with their swimming-specific informational support being the single most unappreciated aspect of social support. Teammates provided a sense of affiliation and shared experience that was described as the most positive aspect of their swimming involvement. The current qualitative findings provide new insights into the concurrent structural, functional, and perceptual dimensions of social support in female youth elite sport.